2006
DOI: 10.1007/s10620-006-9348-1
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Irritable Bowel Syndrome Among Community Subjects With Previous Acute Enteric Infection

Abstract: The purpose of this study was to determine the incidence of postinfectious irritable bowel syndrome (IBS) among community subjects with positive stool studies. This was a prospective cohort study whereby all individuals with stool-positive acute enteric infection (AEI) were recruited from 3 health regions in Ontario, Canada. Each person completed questionnaires regarding preinfectious bowel habit and their bowel habit 3 months postinfection. Manning and Rome I criteria were used to diagnose irritable bowel syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 31 publications
3
54
1
3
Order By: Relevance
“…The aetiology, pathogenesis and prognosis of IBS are not well understood and there is no widely effective treatment [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aetiology, pathogenesis and prognosis of IBS are not well understood and there is no widely effective treatment [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter, Shigella, Salmonella and Escherichia coli infections as well as viral agents, including norovirus, and parasites have been associated with PI-IBS [5,21,[23][24][25]. It has been hypothesized that exposure to an infectious organism alters gut flora, increases intestinal permeability and triggers chronic inflammation, inducing PI-IBS [3,9,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, an outbreak of viral gastroenteritis was associated with the new onset of an IBS-type syndrome in 24% of affected subjects when interviewed 3 months later; subsequent follow-up suggested that postviral IBS was more transient than its bacterial counterpart . Postinfectious IBS may explain only a minority of cases of IBS (1-6.7% in one recent study [Borgaonkar et al 2006]) but it does represent a clear link between exposure to an environmental agent, inflammation and IBS in predisposed individuals (Figure 2). …”
Section: Postinfectious Ibsmentioning
confidence: 99%
“…Post-infectious IBS may explain only a minority of cases of IBS [1-6.7% in one recent study (38)] but it does represent a clear link between exposure to an environmental agent, inflammation and IBS in predisposed individuals.…”
Section: Post-infectious Ibsmentioning
confidence: 99%